2015
DOI: 10.1155/2015/373769
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mandibular Retrusive Deviation on Prefrontal Cortex Activation: A Functional Near-Infrared Spectroscopy Study

Abstract: The objective of this study was to evaluate occlusal condition by assessing brain activity in the prefrontal cortex, which is associated with emotion. Functional near-infrared spectroscopy (fNIRS) was used to detect changes in cerebral blood flow in the prefrontal cortex of 12 healthy volunteers. The malocclusion model was a custom-made splint that forced the mandible into retrusion. A splint with no modification was used as a control. The cortical activation during clenching was compared between the retrusive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
(33 reference statements)
1
9
0
Order By: Relevance
“…Reduced masticatory stimulation might lead to cognitive decline through decreases in cerebral blood flow, decreases in activation of the cortical area and blood oxygen levels, particularly to the frontal cortex [12,13].…”
Section: Agingmentioning
confidence: 99%
“…Reduced masticatory stimulation might lead to cognitive decline through decreases in cerebral blood flow, decreases in activation of the cortical area and blood oxygen levels, particularly to the frontal cortex [12,13].…”
Section: Agingmentioning
confidence: 99%
“…Hence, we considered that prefrontal chewing cognition in elderly edentulous subjects could be evaluated by this technique during chewing performance with and without use of a denture prosthesis. fNIRS is considered to be suitable for examinations of prefrontal activities during chewing performance with and without wearing a denture in clinical conditions, as several previous studies utilized it to detect prefrontal activities during jaw clenching [ 32 ] and chewing [ 28 , 55 , 56 ]. In the present study, we attempted to determine the qualities of prefrontal activities in partially edentulous elderly individuals during chewing while wearing a denture as compared with young healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review reported that tooth loss predicts cognitive decline, because tooth loss might reduce mastication‐induced sensory stimulation and lead to poor nutritional intake . Another study reported that the occlusal condition affects the activation of the brain through blood flow . Animal experiments using mice reported that extraction of molar teeth resulted in learning and memory deficits .…”
Section: Introductionmentioning
confidence: 99%
“…11 Another study reported that the occlusal condition affects the activation of the brain through blood flow. 12 Animal experiments using mice reported that extraction of molar teeth resulted in learning and memory deficits. 13 In humans, one cross-sectional study suggested that the posterior occlusal support is associated with cognitive function, and that a lack of posterior occlusal support influences cognitive decline to a greater extent than the number of teeth alone.…”
Section: Introductionmentioning
confidence: 99%